Nanoparticle Therapy Is a Promising Approach in the Management and Prevention of Many Diseases: Does It Help in Curing Alzheimer Disease? - Lamyaa M. Kassem; Nada A. Ibrahim; S. Ayesha Farhana (Journal of Nanotechnology)
Treatment of brain diseases is always limited by the physiological nature of the highly selective blood-brain barrier (BBB) and the electrostatic charge of the nanoporous extracellular matrix. Nanomedical application provides a promising drug delivery revolution for the treatment of neurodegenerative diseases (NDDs). It depends on improving the pharmacokinetic distribution of drugs through the central nervous system. Nanotechnology offers various forms of nanoparticles, and these nanoparticles have brain-targeted and long-acting properties with minimal systemic adverse effects and motor complications. Gene delivery vehicles and nanocarriers including neurotrophic factors are promising therapeutics for many NDDs, and they can modulate neuronal survival and synaptic connectivity. Neurotrophic factors when integrated with the nanotechnological approaches can pass the BBB merely, representing a significant challenging track. Clinical trials proved that levodopa nanoparticles cause little motor complications which is a considerable drawback in treating Parkinson’s disease with levodopa. Recently, nanotechnology had patented new formulations and achieved various advanced procedures for management, and even prevention, of NDDs. Nanotechnology can be integrated into neuroscience to fight against neurodegenerative diseases. Primary research studies in using nanoparticles to cure Alzheimer disease (AD) are promising but are still in need for more investigations. The present paper aims to review, outline, and summarize various efforts done in the field of using nanoparticles in the management of Alzheimer.